Nora’s Metamorphosis from A Doll Child into A Reasonable Human Being (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2020)
Henrik Ibsen is deemed to be one of the major Norwegian playwrights of the late 19th century whose famous play A Doll’s House manifests a wide variety of social and individual concerns, some of which transcend times and ages and thus become all-time contemporary. This paper mainly focuses on one such concern of an individual- Nora Helmar’s quest of self-identity- which gets unfolded through many other interrelated social issues that altogether result in her complete transformation. This study identifies how Nora who we notice at the beginning of the play as a naïve and submissive woman, changes herself into an outspoken, autonomous and unyielding human being towards the end of the play. It also attempts to highlight Nora’s numerous struggles against the patriarchal hegemony of the society and outlines how these struggles contribute to developing in her a sense of progressive self-awakening which eventually shapes her self-identity as an independent woman, the ultimate destination of her journey of self-discovery. This study finally explores the underlying forces both from within and outside the family working as catalysts behind making Nora a metamorphosed one.